Exploring critical digital literacy in a higher education EFL classroom: Teachers’ views and practices - Hapsari Mutya Rini; Salim Nabhan (ELT Forum: Journal of English Language Teaching, 2023)
Critical digital literacy is increasingly an issue in today’s technology-driven world, and it has been implanted into the Indonesian higher education curriculum to equip students with the ability to critically engage with digital information. Research related to critical digital literacy, especially in EFL settings at a higher education level is still under-explored. Therefore, in this study, the researchers aimed to explore teachers' views on critical digital literacy and their practices in integrating critical digital literacy in EFL classrooms at the university level. This research used a qualitative case study approach. The researchers collected data from three EFL classroom teachers at one of the universities in Surabaya, Indonesia. To validate the data, the researcher used data triangulation, where the data were collected from semi-structured interviews, observation, and document reviews. The data were then analyzed using thematic analysis. The data revealed two main themes including teachers' views on critical digital literacy in EFL classrooms and teachers' practices on critical digital literacy in EFL classrooms. Teachers’ views on critical literacy in EFL classrooms included their understanding of the critical use of technology, their recognition of the importance of students’ critical digital literacy, and the inclusion of critical digital literacy in language learning in accordance with technology development. Additionally, teachers’ practices of critical digital literacy entail the provision of various online materials and platforms, the analysis of the internet sources for students’ digital materials, the involvement of multimodal text in the learning process, and the students’ identity development in digital media. The findings of the study shed light on the various dimensions of critical digital literacy, suggest practical insight on the integration of literacy in EFL classrooms, and call for further development on effective instructional approaches that support the use of technology that promotes critical digital literacy at the university level.